2005
DOI: 10.4049/jimmunol.175.6.3542
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Xenogeneic β2-Microglobulin on Functional Recognition of H-2Kb by the NK Cell Inhibitory Receptor Ly49C

Abstract: NK cells maintain self-tolerance through expression of inhibitory receptors that bind MHC class I (MHC-I) molecules. MHC-I can exist on the cell surface in several different forms, including “peptide-receptive” or PR-MHC-I that can bind exogenous peptide. PR-MHC-I molecules are short lived and, for H-2Kb, comprise ∼10% of total MHC-I. In the present study, we confirm that signaling through the mouse NK inhibitory receptor Ly49C requires the presence of PR-Kb and that this signaling is prevented when PR-Kb is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…In addition, some NK receptors recognize peptide-empty MHC molecules (HLA-G and H-2K b ; Benoit et al, 2005;Gonen-Gross et al, 2005), thus supporting the view that open MHC-I conformers can serve as cis-trans recognition structures. Although our results agree with the genomic/epidemiological data to support an important role for HLA-C in HIV-1 infection, the molecular mechanisms of this role remain obscure.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, some NK receptors recognize peptide-empty MHC molecules (HLA-G and H-2K b ; Benoit et al, 2005;Gonen-Gross et al, 2005), thus supporting the view that open MHC-I conformers can serve as cis-trans recognition structures. Although our results agree with the genomic/epidemiological data to support an important role for HLA-C in HIV-1 infection, the molecular mechanisms of this role remain obscure.…”
Section: Discussionmentioning
confidence: 80%
“…The first bona fide assessment of "altered self" examined the role of peptide in NK cell recognition by Ly49 molecules in vitro (45) ϩ NK cells without significantly altering MHC-I expression profiles (29,33,34). From this we concluded that NK cells can distinguish between self-and modified self-H-2K b molecules via Ly49C.…”
Section: Discussionmentioning
confidence: 99%
“…As well, ␤ 2 m (either mouse or bovine derived) present in vitro or in vivo may be recombining with the Tg H-2K b molecules and thus facilitating transfer. In particular, bovine ␤ 2 m present in the assays may be relevant to our system in that it has previously been shown that bovine ␤ 2 m present in culturing serum can contribute to the formation of a viable interface for Ly49C binding to H-2K b (29). A third possibility is that there is another (unknown) Ly49 molecule that is equally represented in the Ly49C ϩ/Ϫ fractions that can bind with sufficient affinity to H-2K b bound by h-␤ 2 m and can mediate uptake of these hybrid H-2K…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations